Evaluating pedagogical approaches in business education: a comparative analysis - Suharsono, Naswan; Hidayat, Rachmad; Zen, Fadia; Rusmana, Dede; Permansah, Sigit (Journal of Education and Learning (EduLearn), 2025)
The emergence of entrepreneurial groups from university students and alumni can trigger the nation's economic advancement. This study investigated the impact of project-based learning (PJBL) models in enhancing students' business management abilities, integrating components such as resource management, financial-administrative structuring, production, marketing, and business development planning. The research aimed to analyze the most effective teaching methods for business education students to improve learning outcomes in business management skills. The research design adopted a pre-post test format with three phases: treatment phase, test phase, and data analysis phase. The data analysis techniques used included Spearman and Kendall's correlation, Friedman, Kendall's W, Kruskal-Wallis, U test, and Wilcoxon test. The results indicated a significant difference, p0.05, between treatments. Based on the mean rank, the PJBL treatment had the highest mean rank value (3.77; 3.77; 110.40), followed by the problem-based learning (PBL) treatment (2.94; 2.94; 87.14), problem-solving (PS) treatment (1.83; 1.83; 50.67), and finally the traditional learning (TL) treatment (1.46; 1.46; 33.79). This research serves as a recommendation policymaker, educators, students, and any individual aiming to enhance business management skills consider PJBL as a primary treatment or PBL and PS as alternative options.